Evaluation of the effect of several moisturizing creams using the low frequency electrical susceptance approach - Bari Dindar S.; Ali Zana K.; Hameed Soleen A.; Yacoob Aldosky Haval Y. (Journal of Electrical Bioimpedance)
Moisturizers are cosmetic compounds designed to increase the moisture content of the skin. There are many types of these products in the market making it difficult for consumers to select the most effective moisturizer according to their age and gender. Hence, the aim of this study was to evaluate the effects of different moisturizers on skin hydration as well as to figure out any dependencies of the effects of these products on age or gender-related differences. We investigated the short-term moisturizing effects of five different skin moisturizers on 60 participants by using a low frequency electrical instrument. Skin surface susceptance was recorded and compared before and after the application of moisturizers. Statistically significant differences were observed in the moisturizing effect among different types of products. However, with respect to gender and age differences, there were insignificant differences in the effects of the moisturizers. Results of this study suggest that some types of moisturizers that exist in the markets are not as effective as required, which calls for a further evaluation of the moisturizers before entering markets and offering them for sale. In addition, findings suggest that gender or age differences are perhaps not important to consider in the application of moisturizers.